PENENTUAN PRIORITAS LOKASI GUDANG DISTRIBUSI GAS ELPIJI DENGAN MOTODE ANALYTiCAL HIERACHY PROCESS PADA PT. PGS - R RUHELI (Teknik Industri Fakultas Teknik UNIGAL, 2024)
PT. PGS is a private company which operates in the field of LPG gas distribution services and is currently improving the quality of gas distribution services to consumers so the company must continue to make improvements. The current warehouse location is only in Ciamis City which is intended to serve the needs of Ciamis District and its surroundings and in Kawali to serve the needs of North Ciamis. The problem currently faced by the company is that there is no warehouse to serve the LPG gas needs for the southern Ciamis area, including the Pangandaran area. The aim of this research is to determine the appropriate warehouse location for LPG gas distribution in the southern Ciamis area. Determining the location of the warehouse is carried out by considering the criteria and alternatives which are carried out using a quantitative assessment model. The method used is Analytical Hierarchy Process (AHP). namely the decision making process which basically is choosing an alternative. The data collection technique is carried out through questionnaires. The research results show that the warehouse location in Banjarsari District is the first priority because it has the highest value, namely 0.441 or 44.1%, then followed by Padaherang District with 0.275 or 27.5%, then Kalipucang District with 0.189 or 18.9%, and finally Pangandaran District with 0.095. or 9.5%.Keywords: Location Determination and Analytical Hierachy Process